Protease-Resistant, Broad-Spectrum Antimicrobial Peptides with High Antibacterial and Antifungal Activity - Tanil Kocagoz; Betul Zehra Temur; Nihan Unubol; Merve Acikel Elmas; Zeynep Kanlidere; Sumeyye Cilingir; Dilan Acar; Gizem Boskan; Sumeyye Akcelik Deveci; Esma Aybakan; Aslihan Ozcan Yoner; Neval Yurttutan Uyar; et al. (Life)
Antimicrobial peptides (AMPs) are a diverse group of small, naturally occurring molecules that orchestrate the innate immune response of various organisms, from microorganisms to humans. Characterized by their broad-spectrum activity against bacteria, fungi and viruses, AMPs are increasingly recognized for their potential as novel therapeutic agents in the face of rising antibiotic resistance. Here, we present several newly designed AMPs, one of which, DTN6, exerts significant activity against several organisms with MIC values as low as 0.5 µg/mL. The D-TN6 peptide influences both bacteria and yeasts. Scanning electron microscopy and transmission electron microscopy results showed that the bacterial membrane is affected by D-TN6, which is resistant to proteases and is effective against antibiotic-resistant pathogens with hemolytic activity and low toxicity. The D-TN6 peptide is effective in vivo against standard S. aureus strains in wounds. Thus, D-TN6 is a potent antibiotic candidate with a broad spectrum of activity. Overall, AMPs are a promising tool for the development of next-generation antimicrobial agents that could mitigate global health threats posed by multidrug-resistant pathogens.